2013
DOI: 10.1186/2193-1801-2-218
|View full text |Cite
|
Sign up to set email alerts
|

An audit to determine if vitamin b12 supplementation is necessary after sleeve gastrectomy

Abstract: Sleeve gastrectomy has increased in popularity over the last five years and it is likely to supersede gastric banding. Nevertheless, it is unclear whether vitamin B12 supplementation is required after surgery. The aim of this short report is to identify any vitamin B12 deficiency and highlight the necessity of post laparoscopic sleeve gastrectomy vitamin B12 monitoring.Patients and methodsA review of 66 patients underwent LSG in our institution. 25 patients were excluded as they had no postoperative vitamin B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Moreover, there is another study which has reported that in 41 patients having udergone BS, vitamin B12 deficiency was 20% post-operatively [22] . In addition,…”
Section: Methodsologymentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, there is another study which has reported that in 41 patients having udergone BS, vitamin B12 deficiency was 20% post-operatively [22] . In addition,…”
Section: Methodsologymentioning
confidence: 99%
“…Its preoperative prevalence ranges between 3-18% [22][23][24][25]. After bariatric surgery the absorption of the B12 may be impaired at different levels depending on the type of procedure.…”
Section: Methodsologymentioning
confidence: 99%
See 3 more Smart Citations